THE CONSTRUCTION OF ĀYĀTUL AḤKĀM (Constructing the Selection Bases of Āyātul Aḥkām) - Ahmad Sholihin Siregar (AHKAM : Jurnal Ilmu Syariah, 2018)
The Construction of Legal Verses (Constructing Selection Bases of Legal Verse). The questions to answer in this research is how to select legal verse from non legal verses, what its characterstics are and how many verses Quran contains legal verses. Therefore this research aimed to construct a basis in selecting legal verse, its characteristic and its number in Quran. This basis must be constructed regarding to the unavailability of selection basis previously constructed. The research is a normative legal research (dogmatic, doctrinaire). The objects are Quran verses with mimetic and objective approach. In this research, foundation of Quran verses selection consisting textual and contextual basis is established. Writers found 418 legal verses using textual and contextual bases and its characteristics.